Y and Fe co-doped LaNiO3 perovskite as a novel bifunctional electrocatalyst for rechargeable zinc-air batteries. (12th March 2023) - Lu, Zeming; Zhou, Hang; Qian, Bin; Wang, Shun; Zheng, Yifeng; Ge, Lin; Chen, Han
Abstract: Perovskite oxides are widely regarded as the promising air electrode catalytic materials for zinc-air batteries (ZABs). In the present work, A-site Y and B-site Fe co-doped La0.85 Y0.15 Ni0.7 Fe0.3 O3 perovskite catalyst was prepared by self-propagating high-temperature synthesis, and this material was evaluated as a bifunctional electrocatalyst for ZABs. The effect of co-doping on crystal structure and reaction activities, which can promote oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), was investigated. Results show that Y and Fe co-doping substantially improved the ORR and OER of LaNiO3 . In comparison with LaNiO3, the ORR performance of La0.85 Y0.15 Ni0.7 Fe0.3 O3 exhibited a higher limiting current density (3.8 mA cm −2 at 0.4 V vs. RHE) and more positive onset potential (0.75 V vs. RHE) at 1600 rpm. It also had an excellent OER performance of 1.74 V vs. RHE at 10 mA cm −2 . When La0.85 Y0.15 Ni0.7 Fe0.3 O3 was used as an air electrode catalyst for ZABs, it exhibited a high power density of 93.6 mW cm −2, which increased by 84.8% compared with that of LaNiO3 . Moreover, the full cell with La0.85 Y0.15 Ni0.7 Fe0.3 O3 air electrode catalyst was operated for more than 80 h, maintaining good stability. Therefore, La0.85 Y0.15 Ni0.7 Fe0.3 O3 can be used as a promising bifunctional air electrode catalyst for ZABs. The characterization analysis reveals that A-site Y and B-site Fe co-doped catalyst transforms crystal structure from trigonal system to cubic system, retain the valence state of Ni 3+ and increases the contents of O2 2− /O −, and these properties are more conducive for LaNiO3 catalysis. Graphical abstract: Image 1 Highlights: A-site Y and B-site Fe co-doped La0.85 Y0.15 Ni0.7 Fe0.3 O3 is studied as a bifunctional electrocatalyst for Zinc air battery. The battery shows a power density as high as 93.6 mW cm −2 when La0.85 Y0.15 Ni0.7 Fe0.3 O3 was used as cathode catalyst. La0.85 Y0.15 Ni0.7 Fe0.3 O3 presents excellent long-term stability that operated stably for more than 80 h.